Serotoninergic receptors in the anteroventral preoptic region modulate the hypoxic ventilatory response - Gargaglioni, Luciane H.; Bicego, Kenia C.; Nucci, Tatiane B.; Branco, Luiz G. S. (Elsevier B.V., 2006)
Hypothalamus is a site of integration of the hypoxic and thermal stimuli on breathing and there is evidence that serotonin (5-HT) receptors in the anteroventral preoptic region (AVPO) mediate hypoxic hypothermia. Once 5-HT is involved in the hypoxic ventilatory response (HVR), we investigated the participation of the 5-HT receptors (5-HT1, 5-HT2 and 5-HT7) in the AVPO in the HVR. To this end, pulmonary ventilation (V-E) of rats was measured before and after intra-AVPO microinjection of methysergide (a 5-HT1 and 5-HT2 receptor antagonist), WAY-100635 (a 5-HT1A receptor antagonist) and SB-269970 (a 5-HT7 receptor antagonist), followed by 60 min of hypoxia exposure (7% O-2). Intra-AVPO microinjection of vehicles or 5-HT antagonists did not change VE during normoxic conditions. Exposure of rats to 7% O-2 evoked typical hypoxia-induced hyperpnea after vehicle microinjection, which was not affected by methysergide. WAY-100635 and SB-269970 treatment caused an increased HVR, due to a higher tidal volume. Therefore, the current data provide the evidence that 5-HT acting on 5-HT1A and 5-HT7 receptors in the AVPO exert an inhibitory modulation on the HVR. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: control of breathing; ventilation; Hypoxia; serotonin; preoptic area; rats; hypoxic ventilatory response